(-4,4) , (4,4)

Slope is equal to the change in y over the change in x, or rise over run.

m=change in ychange in x

The change in x is equal to the difference in x-coordinates (also called run), and the change in y is equal to the difference in y-coordinates (also called rise).

m=y2-y1x2-x1

Substitute in the values of x and y into the equation to find the slope.

m=4-(4)4-(-4)

Simplify.

Reduce the expression by cancelling the common factors.

Cancel the common factor of 4-(4) and 4-(-4).

Rewrite 4 as -1(-4).

m=-1⋅-4-(4)4-(-4)

Factor -1 out of -1(-4)-(4).

m=-1(-4+4)4-(-4)

Reorder terms.

m=-1(-4+4)4-4⋅-1

Factor 4 out of -1(-4+4).

m=4(-1(-1+1))4-4⋅-1

Cancel the common factors.

Factor 4 out of 4.

m=4(-1(-1+1))4(1)-4⋅-1

Factor 4 out of -4⋅-1.

m=4(-1(-1+1))4(1)+4(1)

Factor 4 out of 4(1)+4(–1).

m=4(-1(-1+1))4(1+1)

Cancel the common factor.

m=4(-1(-1+1))4(1+1)

Rewrite the expression.

m=-1(-1+1)1+1

m=-1(-1+1)1+1

m=-1(-1+1)1+1

Add -1 and 1.

m=-1⋅01+1

m=-1⋅01+1

Simplify the denominator.

Multiply -1 by -1.

m=-1⋅01+1

Add 1 and 1.

m=-1⋅02

m=-1⋅02

Simplify the expression.

Multiply -1 by 0.

m=02

Divide 0 by 2.

m=0

m=0

m=0

m=0

Substitute the value of m into the slope-intercept form of the equation, y=mx+b.

y=(0)⋅x+b

Substitute the value of x into the slope-intercept form of the equation, y=mx+b.

y=(0)⋅(-4)+b

Substitute the value of y into the slope-intercept form of the equation, y=mx+b.

4=(0)⋅(-4)+b

Rewrite the equation as (0)⋅(-4)+b=4.

(0)⋅(-4)+b=4

Simplify (0)⋅(-4)+b.

Multiply 0 by -4.

0+b=4

Add 0 and b.

b=4

b=4

b=4

The values of the slope and y-intercept are m=0 and b=4.

m=0

b=4

Find the Slope and Y-Intercept (-4,4) , (4,4)